The effectiveness of BEMER physical vascular therapy in the condition after closed repositioning of right femoral shaft fracture. A case study - Jazdończyk, Paulina (Journal of Education, Health and Sport, 2018)
Introduction. Blood vessels of microcirculation account for about 99% of the total count (1011) of an adult’s blood vessels. According to the producer, BEMER Vascular Therapy is the most effective and most researched form of physical therapy available. The main objective of the study was to assess the usefulness of BEMER therapy in the correction of swelling after closed repositioning of right femoral shaft fracture.Material. Female aged 64. Diagnosis: the condition after closed repositioning of right femoral shaft fracture using a femur nail Synthes Expert RFN 320 mm, 10mm. Physiotherapeutic proceedings. The proceedings implemented on the second day following discharge from a hospital included: lymphatic drainage and kinesitherapy focused on upright standing, improvement of muscle strength in the lower limb, correction of movement deficit in the hip and knee joint by means of PNF method. The proceedings performed from 06.02. to 22.03.2018 did not bring the expected results, therefore, on 23.03.2018 lymphatic drainage was replaced with general and local physical vascular therapy using the Bemer Classic apparatus.Summary. The analysis of subsequent measurements revealed no progress in the applied physical therapy. The cause of failure in the correction of the swelling in the operated lower limb may be a short period of therapy lasting only eight days. Another cause may be too long nails connecting right femoral shaft fracture which may generate inflammation of the limb. The displayed therapeutic process in this case cannot be interpreted as a recommendation to apply or not apply the therapy and only a direction for further studies.